Secrecy Cognitive Gain of Cognitive Radio Sensor Networks with Primary Outage Constraint. (11th June 2015) - Ma, Hongyu; Niu, Kai; Wu, Weiling; Li, Shengyu; Chu, Guangqian
Abstract : This paper studies the physical layer security issue for cognitive radio sensor networks (CRSNs) with primary outage constraint, for which a tractable framework is developed to analyze the secrecy performance for CRSNs related to the random channel characteristics, the spatial distributions of nodes, the nearest neighbour routing protocol, and the aggregate interference. Based on stochastic geometry technique, a novel random analysis method is proposed to derive the closed-form expression of secrecy transmission capacity and analyze the connection outage probability (COP) and secrecy outage probability (SOP) for both secondary (SR) and primary (PR) systems. Then, the concept of secrecy cognitive gain is produced to highlight the effect of SR systems with secrecy on the whole networks security. Comparing with a single PR system, the SR system is beneficial to enhance the secrecy level for overlaid CRSNs. In addition, the maximum achievable secrecy capacity is achieved through optimizing the density of SR systems satisfying outage constraints of PR and SR systems. Analytical results provide insights into regimes in which the SR system with secrecy is beneficial for the overlaid network secrecy.